Politik Hukum dalam Otonomi Daerah Berbasis Keadilan Bermartabat - Tjahjana, Teguh Pribadi (FOCUS, 2025)
One of the subsystems of national development legal politics is the legal policy for the formation of regional regulations. Given that the values, philosophies, theories, principles and norms of the state, all of which are influenced by the national legal system and politics, bind and become guidelines for regional legal products, especially regional regulations, this has additional meaning. The issue is how regional autonomy can have an impact on the welfare of the Indonesian people. How does the legal system of regional autonomy adhere to the principles of dignified justice? The results of his research show that regional autonomy can be one of the instruments for accelerating the development of the welfare of the Indonesian people, provided that regional development must refer to geographical or regional potential, governance, especially with regard to the government bureaucracy itself, and the implementation of minimum service standards by local governments that ensure an evenly distributed improvement in the quality of public services to improve people's welfare, promote democratic life, justice, equity, and maintain good relations between the center and the regions, as well as between regions, in order to maintain the integrity and unity of the Unitary State of the Republic of Indonesia.